THE REFLECTION OF THE IDEA OF REPATRIATION OF THE ARMENIAN DEPORTEES IN DJAGADAMART (BATTLE), HAIRENIK (HOMELAND) AND ASBAREZ (ARENA) PERIODICALS IN 1920 - Hovhannisyan, Lilit (Armenian Folia Anglistika, 2025)
In 1920, the periodicals Djagadamart (Constantinople) and Hairenik  (Boston), Asbarez (Fresno) published an interesting analysis on the issue of returning deported Armenians to their homeland. The political sections of newspapers emphasized the significance of addressing the issues related to the deprivation of the Armenians from their homeland, their exile, and their right to return within the context of the current Middle East situation. They have also covered the Paris International Peace Conference, the Eastern policies of the Allied Powers, and the foreign policy pursued by the First Republic of Armenia. In this context, the publications regarding the Sevres Treaty signed on August 10, 1920 and the Arbitral Award of the U.S. President Woodrow Wilson regarding the Armenian-Turkish border on November 22nd are of particular interest. These periodicals have made valuable contributions to clarifying safeguards for the safety and security of Western Armenians, and promoting ideas for an Independent and United Armenia. Challenges to the concept of repatriating deported Armenians back to their homeland have also been raised in the pages of the above-mentioned publications. The topic is relevant as the periodicals Djagadamart, Hairenik, Asbarez are being presented for the first time within the context of discussing the issue of repatriation of deported Armenians.
Keywords: Western Armenia; Republic of Armenia; Cilicia; Armenian Genocide; homeland; idea of an Independent and United Armenia